The Effect of Arabic-Language Animated Films on Listening and Speaking Skills: A Quasi-Experimental Study of Madrasah Students - Muh. Hafizin Yusri; Khaerul Muttakin; Muhammad Khairul Fatihin (Lembaga Sosial Rumah Indonesia, 2026)
Purpose – This study examines the effect of animated cartoons as a learning medium on students’ listening and speaking skills in Arabic language instruction.Methods – The study employed a quasi-experimental pretest–posttest non-equivalent control group design involving eleventh-grade students at MA Darul Kamal NW Kembang Kerang. Using purposive sampling, students were assigned to an experimental group (n = 25) taught with Arabic cartoon animation films and a control group (n = 28) receiving conventional instruction. Data were collected through validated listening and speaking tests and analysed using the Mann–Whitney U test and ANCOVA, with effect sizes and 95% confidence intervals reported. Findings – The experimental group outperformed the control group in the posttest (M = 86.20 vs. 70.96). The Mann–Whitney U test revealed a significant difference with a large effect size (p < .001; r = 0.78). This result was confirmed by ANCOVA, which showed a significant treatment effect after controlling for baseline scores (F = 32.25, p < .001; partial ?² = 0.57). Overall, animated cartoons significantly enhanced students’ listening and speaking skills, with a stronger effect on listening. Research Implications – The findings of this study have practical implications for Arabic language learning, particularly the use of animated audiovisual media as a routine learning strategy to improve students' listening and speaking skills in a more interactive, student-centered manner.